The extremely cold 2009-2010 winter and its relationship with the Arctic oscillation - Wen, Xin-Yu; Hu, Yong-Yun; Liu, Ji-Ping (Frontiers of Physics, 2013)
The Northern-Hemisphere high-latitude continents experienced extremely cold weathers in winter 2009-2010. In the present paper, we show that the cold winter was associated with the activity of the Arctic oscillation (AO), which demonstrated the strongest negative polarity over the past six decades and persisted from December, 2009 to March, 2010. It is found that variations of the surface AO was closely linked to stratospheric polar vortex anomalies, and that the surface AO phases followed downward propagation of stratospheric Northern-Hemisphere Annular mode (NAM) anomalies during the winter. The case of 2009-2010 winter provides us with a typical example that anomalous stratospheric signals can be used to improve skills of long-range weather forecast and intra-seasonal climate prediction in winter time. We also show that the El Nino event, which started developing from May 2009, might contribute the formation of exceptionally negative and persistent AO and stratospheric NAM, particularly over North Pacific and North America. Physics, Multidisciplinary SCI(E) 中国科学引文数据库(CSCD) 0 ARTICLE 5 590-603 8